Visual disturbances in people after stroke and the possibility of adaptation of printed materials for people with aphasia - Kokot, Magdalena (Interdyscyplinarne aspekty diagnozy i terapii logopedycznej, 2020)
Every year, approximately 60–70,000 people suffer from stroke in Poland, a significant proportion of whom are over 60 (Kwolek, 2009). Up to 70% of these patients are affected by severe visual deficits resulting from stroke alone (Benshir, 2016). Some of the patients with stroke had been sufferde onset of sight diseases such as: AMD „age-related macular degeneration”, cataracts, glaucoma, diabetic retinopathy (Smith i in., 2018) before the stroke. In vision deficits resulting from stroke or age-related eye diseases, eyeglass correction is sometimes too little to improve vision quality, and consequently rehabilitation and life after stroke. This article aims to introduce the issue of visual impairment in people after stroke and indicate possible ways to increase the effectiveness of therapy based on own research.